2017
DOI: 10.18869/acadpub.jnkums.9.1.135
|View full text |Cite
|
Sign up to set email alerts
|

The study of effectiveness metacognitive techniques educationon life style of married women nurses in Bojnoord

Abstract: Background & Objectives: Different studies show that metacognitive techniques education is effective in mental health and life improvement. This study aims to investigate the effectiveness of metacognitive techniques education (mindfulness and attention training) on life style of nurses at Bojnord City. Materials and Methods: This study is semi-experimental (pretest-posttest with control groups). In the present study the statistical population includes all nurses in Bojnord City in 2015. Among them, 30 nurses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The result about metacognition is in agreement with previous results (Castro Muñoz et al, 2021;Lenzo et al, 2020;Nameni et al, 2017;Palmieri et al, 2021;Cinar & Schou, 2014) and the result about emotion regulation training is in agreement with that of other studies (Miller et al, 2018;Morawetz et al, 2020;Pachón-Basallo et al, 2021;Steward et al, 2019;Gomez & Perez, 2020;Isasi et al, 2013;Ferrer & Mendez, 2018;Babaei et al, 2021). To explain the results obtained about metacognitive training, it can be said that according to the theory of self-regulation of executive function (S-REF), metacognitive training affects self-regulation through negative relationship with cognitive attention syndrome (CAS) and self-regulation has a positive relationship with selfefficacy (Kaplan, 2008;Salari Far & Mazaheri, 2010;Cera et al, 2013;Pour vakhshoori et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…The result about metacognition is in agreement with previous results (Castro Muñoz et al, 2021;Lenzo et al, 2020;Nameni et al, 2017;Palmieri et al, 2021;Cinar & Schou, 2014) and the result about emotion regulation training is in agreement with that of other studies (Miller et al, 2018;Morawetz et al, 2020;Pachón-Basallo et al, 2021;Steward et al, 2019;Gomez & Perez, 2020;Isasi et al, 2013;Ferrer & Mendez, 2018;Babaei et al, 2021). To explain the results obtained about metacognitive training, it can be said that according to the theory of self-regulation of executive function (S-REF), metacognitive training affects self-regulation through negative relationship with cognitive attention syndrome (CAS) and self-regulation has a positive relationship with selfefficacy (Kaplan, 2008;Salari Far & Mazaheri, 2010;Cera et al, 2013;Pour vakhshoori et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…The study of Keng (26) also found that mindfulness was accompanied by growth in hope and optimism, and generally improved psychological well-being of individuals in clinical settings such as a hospital and nonclinical settings such as educational centers. Nameni et al in a study on the effectiveness of teaching meta-cognitive methods on nursing life style showed that attention and mindfulness education has been effective on lifestyle of employed and married nurses, by contributing significant changes in health and promoting lifestyle to their mental and physical health (3). Ghashgaee et al also revealed that Mindfulness Based Cognitive Therapy (MBCT) is effective in improving the quality of life and physical and mental dimensions of patients (27).…”
Section: Health-promoting Lifestyle Profile (Hplp)mentioning
confidence: 99%
“…According to the World Health Organization (WHO), chronic diseases will be the main cause of death and disability in 2020, and will account for two thirds of all diseases (2). Nowadays, many physical illnesses are considered as psychosomatic disease associated with lifestyle (3). Lifestyle is a multi-dimensional phenomenon that contains all aspects of everyday life including sleep, food, health, customs, work, gaming, entertainment, time spent, social relationships, and way of thinking, behavior, feelings and emotions.…”
mentioning
confidence: 99%